2023
DOI: 10.1371/journal.pntd.0011826
|View full text |Cite
|
Sign up to set email alerts
|

Scabies prevalence and its associated factors among prisoners in southern Ethiopia: An institution-based analytical cross-sectional study

Efa Ambaw Bogino,
Beshada Zerfu Woldegeorgis,
Lantesil Wondewosen
et al.

Abstract: Background Scabies is an ectoparasitic infestation that can easily spread during close human contact and in overcrowded areas such as prisons and public places where sanitation is a problem. Globally, as many as 300 million people are infested with scabies each year. Within Ethiopia, its burden in institutions like prisons is not well-studied. As a consequence, we sought to estimate the prevalence of scabies and also identify factors associated with it among prison inmates in southern Ethiopia. Methods An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“… Confounding factors identified Strategies to deal with confounding factors stated Outcomes measured in a valid and reliable way Was appropriate statistical analysis used? Total score( n = 8) Kouotou, EA [ 44 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Bartosik, K [ 45 ] Yes Yes Yes Yes No No Yes Yes 6 Bogino, E [ 46 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 RAHMATI, R [ 47 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Mannocci, A [ 35 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Harouna, M [ 48 ] Yes Yes …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“… Confounding factors identified Strategies to deal with confounding factors stated Outcomes measured in a valid and reliable way Was appropriate statistical analysis used? Total score( n = 8) Kouotou, EA [ 44 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Bartosik, K [ 45 ] Yes Yes Yes Yes No No Yes Yes 6 Bogino, E [ 46 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 RAHMATI, R [ 47 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Mannocci, A [ 35 ] Yes Yes Yes Yes Yes Yes Yes Yes 8 Harouna, M [ 48 ] Yes Yes …”
Section: Methodsmentioning
confidence: 99%
“…This systematic review also found that hygienic practices were significantly associated with the occurrence of scabies among prisoners, based on included studies [ 44 , 46 , 48 ]. Based on a study conducted in Ethiopia [ 46 ], prisoners who did not use soap during hand washing had 5.53 times [AOR = 5.53; 95% CI: 1.45–21.17] higher odds of exhibiting scabies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations